In silico biomechanical analysis of poller screw-assisted small-diameter intramedullary nail in the treatment of distal tibial fractures - Tan, Jinchuan; Yang, Yang; Wang, Mian; Huang, Xuecheng; Ouyang, Hanbin; Zhao, Dongliang; Huang, Gang; Deng, Yuping; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To evaluate the biomechanical effects of Poller screws (PS) combined with small-diameter intramedullary nails in the treatment of distal tibial fractures at different locations and on different planes. Methods: Nine finite element (FE) models were used to simulate the placement of the intramedullary nail (IMN) and the PS for distal tibial fractures. Structural stiffness and interfragmentary motion (IFM) through the fracture were investigated to assess the biomechanical effects of the PS. The allowable stress method was used to evaluate the safety of the construct. Results: With the axial load of 500 N, the mean axial stiffness of IMN group was 973.38 ± 95.65 N/mm, which was smaller than that at positions A and B of the coronal group and sagittal group (p < 0.05). The shear IFM of the IMN group was 2.10 ± 0.02 mm, which were smaller than that at positions A and B of the coronal group and sagittal group (p < 0.05). Under physiological load, the stresses of all internal fixation devices and the nail-bone interface were within a safe range. Conclusion: In the treatment of distal tibial fractures, placing the PS in the proximal fracture block can obtain better biomechanical performance. The IMN fixation system can obtain higher structural stiffness and reduce the IFM of the fracture end by adding PS.